Natural Molecules From Chinese Herbs Protecting Against Parkinson’s Disease via Anti-oxidative Stress - Ding, Yaqi; Xin, Chenqi; Zhang, Cheng-Wu; Lim, Kah-Leong; Zhang, Hang; Fu, ZhenQian; Li, Lin; Huang, Wei (Frontiers in Aging Neuroscience, 2018)
Parkinson’s disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease, affecting about 7 to 10 million patients worldwide. The major pathological features of PD include loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc) of the midbrain and the presence of α-synuclein-enriched Lewy bodies. Although the mechanism underlying PD pathogenesis remains to be elucidated, oxidative stress induced by the overproduction of reactive oxygen species (ROS) is widely accepted to be a key pathogenic factors. ROS cause oxidative damage to proteins, lipids, and DNA, which subsequently lead to neurodegeneration. Great efforts have been made to slow or stop the progress of PD. Unfortunately there is no effective cure for PD till now. Compounds with good antioxidant activity represent the promising candidates for therapeutics of PD. Some natural molecules from Chinese herbs are found to have good antioxidant activity. Both in vitro and in vivo studies demonstrate that these natural molecules could mitigate the oxidative stress and rescue the neuronal cell death in PD models. In present review, we summarized the reported natural molecules that displayed protective effects in PD. We also addressed the possible signal pathway through which natural molecules achieved their antioxidative effects and mitigate PD phenotypes. Hopefully it will pave the way to better recognize and utilize Chinese herbs for the treatment of PD.